2010
DOI: 10.1029/2009jb007023
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of magma conduits during the 1998–2000 eruptions of Piton de la Fournaise volcano, Réunion Island

Abstract: [1] At basaltic volcanoes, magma is transported to the surface through dikes (magmafilled fractures), but the evolution of these dikes as eruptions proceed is rarely documented. In March 1998, after five and a half years of quiescence, Piton de la Fournaise volcano (Réunion Island) entered into a new eruptive phase characterized by intense eruptive activity. Coeruptive displacements recorded by interferometric synthetic aperture radar (InSAR) for the first five eruptions of the cycle are analyzed using 3-D bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 90 publications
(121 reference statements)
7
90
0
Order By: Relevance
“…Indeed, the data fit breaks down when the southernmost part of the shallow dike is shortened by 5 km and replaced with a 5 km-long dike connecting the eruptive fissure to the deep dike. A similarly narrow path is also postulated for other volcanoes such as Piton de la Fournaise [Fukushima et al, 2010;Traversa et al, 2010].…”
Section: Magma Originmentioning
confidence: 52%
See 1 more Smart Citation
“…Indeed, the data fit breaks down when the southernmost part of the shallow dike is shortened by 5 km and replaced with a 5 km-long dike connecting the eruptive fissure to the deep dike. A similarly narrow path is also postulated for other volcanoes such as Piton de la Fournaise [Fukushima et al, 2010;Traversa et al, 2010].…”
Section: Magma Originmentioning
confidence: 52%
“…[27] Here, following Fukushima et al [2005Fukushima et al [ , 2010 for dikes and Sun et al [2011] for faults, we determine the sources of the observed InSAR displacements by simultaneously inverting for a quadrangular fracture geometry, location and uniform stress changes on the dikes or faults, leading to non-uniform displacement distributions. The method used here [Fukushima et al, 2005] combines 3D numerical models, based on a boundary element numerical method [Cayol and Cornet, 1997], with nonlinear inversions, based on a near neighborhood algorithm [Sambridge, 1999a[Sambridge, , 1999b.…”
Section: Simultaneous Inversion Of Source Geometry Location and Dispmentioning
confidence: 99%
“…At shallower depth, they can migrate laterally, probably because they encounter a level of neutral buoyancy Fukushima et al 2010). The column therefore also acts as a guide for the intrusions.…”
Section: Inter-eruptive Behavior Of Piton De La Fournaisementioning
confidence: 99%
“…Modeling of ground displacements caused by dikes feeding the eruptions (e.g., Peltier et al 2005 and references therein; e.g., Fukushima et al 2010) shows that all the intrusions start at depth and rise vertically in the fractured column. At shallower depth, they can migrate laterally, probably because they encounter a level of neutral buoyancy Fukushima et al 2010).…”
Section: Inter-eruptive Behavior Of Piton De La Fournaisementioning
confidence: 99%
“…They are able to detect even subtle ground movements induced by changes in magma pressure or distribution at depth. Data from these methods are widely used to (i) forecast that an eruption is imminent (Sigmundsson et al 2010) and (ii) infer the geometry of volcanic plumbing system components, such as dykes (Wright et al 2006Fukushima et al 2010, cone sheets (Chadwick et al 2011), sills (Amelung et al 2000;Sigmundsson et al 2010) and magma reservoirs (Chang et al 2007).…”
Section: Ground Deformation Induced By Intrusionsmentioning
confidence: 99%